The influence of regional location on the innovation activity of Spanish firms: A logit analysis. - Manuel Acosta Sero; Daniel Coronado Guerrero (European Regional Science Association (ERSA), 1998)
The set of elements which explain the results of the innovation process undertaken by the firms is an ongoing cause of worry for policy makers. In our case, after analyzing how R+D activities and their results are related to regional development, we will examine the factors which influence investigation activities. Among this factors we shall include both those related to the characteristics of the companies as well as government funding of R+D or the effects of the firms' location. In order to do this a logit model will be created in which the endogenous variable will measure whether or not an enterprise has patented an innovative activity. The final objective of the paper is to provide policy makers with a way of evaluating the results of their policies, as well as to examine the effects of other elements in the process. Keywords: R+D, Regional Development, Technological Policy, Patents.
Keywords: 330